2019
DOI: 10.1111/apha.13367
|View full text |Cite
|
Sign up to set email alerts
|

Myokines in skeletal muscle physiology and metabolism: Recent advances and future perspectives

Abstract: Myokines are molecules produced and secreted by skeletal muscle to act in an auto-, para-and endocrine manner to alter physiological function of target tissues. The growing number of effects of myokines on metabolism of distant tissues provides a compelling case for crosstalk between skeletal muscle and other tissues and organs to regulate metabolic homoeostasis. In this review, we summarize and discuss the current knowledge regarding the impact on metabolism of several canonical and recently identified myokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 105 publications
(501 reference statements)
1
51
0
1
Order By: Relevance
“…It is the only myokine known to be downregulated by acute and chronic endurance- and resistance-type exercise in both rodents and humans [ 115 ]. Its expression is increased in human obesity and strongly associated with insulin resistance by downregulating GLUT4 expression and by decreasing phosphorylation of IRS1 [ 26 ]. On the contrary, inhibition of myostatin upregulates oxidative metabolism in SkM [ 115 ].…”
Section: The Role Of Myokines In Metabolic Pathways During Exercismentioning
confidence: 99%
See 2 more Smart Citations
“…It is the only myokine known to be downregulated by acute and chronic endurance- and resistance-type exercise in both rodents and humans [ 115 ]. Its expression is increased in human obesity and strongly associated with insulin resistance by downregulating GLUT4 expression and by decreasing phosphorylation of IRS1 [ 26 ]. On the contrary, inhibition of myostatin upregulates oxidative metabolism in SkM [ 115 ].…”
Section: The Role Of Myokines In Metabolic Pathways During Exercismentioning
confidence: 99%
“…In addition, METRNL was able to indirectly stimulate M2 Mφ polarization by inducing eosinophils to secrete IL-4 and IL-13 [ 98 ]. Meanwhile, IL-15 was noted to antagonize the detrimental actions of TNF-α, considering its antioxidant properties [ 26 , 87 ] and its ability to stimulate adiponectin release [ 86 ] (6). Likewise, exercise-induced reduction of myostatin by irisin [ 44 ] (7a) was described to reduce availability of myostatin to engage in proinflammatory responses [ 116 ] (7b).…”
Section: An Integrative Overview Of Exercise-induced Factors Influmentioning
confidence: 99%
See 1 more Smart Citation
“…Several AMs send projections to fat body, including AM A4 and AM A5 , which project to the fat body surrounding the male gonad. Whether AM segmentspecific projections play architectural and/or signalling roles via the release of diffusible signals similar to myokines in vertebrates (Das et al, 2019) remains to be fully assessed. The multiple shapes adopted by AMs suggest that they could be passively deformed by the steric volume of internal organs during larval crawling.…”
Section: Specific Morphologies and Internal Organ Connections Of Amsmentioning
confidence: 99%
“…However, one meta-analysis found that early mobilization and rehabilitation had no signi cant effects on muscle strength, quality of life, and ICU-AW incidences, perhaps due to the inadequate inclusion of published randomized controlled trials (RCT) 27 . As for the mechanisms of rehabilitation training on these bene ts, in addition to conventional concepts, skeletal muscles are now considered as important endocrine tissues that secrete various bioactive molecules, called myokines, that act in an auto-, para-, and endocrine manner to regulate the physiological function of target tissues and contribute to the progression of diverse diseases 28,29 . Rehabilitation training is speculated to protect target organs against disorders through the regulation of myokines homoeostasis, but further studies are needed to explore the implications and underlying mechanisms of myokines as related to the bene cial effects of rehabilitation therapy on severe and critical COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%